Functions of potassium channels blocked by low micromolar 4‐aminopyridine in the crayfish nervous system - Goldfeder, Nicole; McDonald, Riley; Gaston, Sarah; Harrison, Amarri; Kim, Dong‐Ho; MacIntosh, Clara; Miranda, Mauricio Moel; Odom, Emma; Nishad, Simmi; Siwik, William; Zhang, Liangzhu; Lin, Jen‐Wei (Synapse (New York, N.Y.), 2022)
4‐aminopyridine (4‐AP) is a potassium channel blocker that has been used to treat patients with multiple sclerosis and Lambert–Eaton disease. The concentration of this drug in the blood of patients was estimated to be in low or submicromolar range. Animal studies have shown that 4‐AP at such low concentration selectively blocks a subset of channels in Kv1 or Kv3 families. The crayfish opener neuromuscular junction and ventral superficial flexor (VSF) preparations were used to examine functions of K+ channels blocked by low concentrations of 4‐AP. At opener motor axons, intracellular recordings show that 4‐AP could increase action potential (AP) amplitude, duration, and after‐depolarization (ADP) at 10 μM. As 4‐AP concentration was increased, in twofold steps, AP amplitude did not increase further up to 5 mM. AP duration and ADP increased significantly mainly in two concentration ranges, 10–50 μM and 1–5 mM. The effects of 50 μM 4‐AP on the VSF were less consistent than that observed at the opener motor axons. 4‐AP did not change AP amplitude of motor axons recorded with an extracellular electrode and change in AP repolarizing potential was observed in ∼25% of the axons. EPSP recorded simultaneously with AP showed an increase in amplitude with 4‐AP treatment only in 30% of the axon‐EPSP pairs. 4‐AP also increased firing frequencies of ∼50% of axons. In four animals, 4‐AP “awakened” the firing of APs from an axon that was silent before the drug. The mixture of positive and negative 4‐AP effects summarized above was observed in the same VSF preparations in all cases (n = 8). We propose that there is a significant diversity in the density 4‐AP‐sensitive potassium channels among motor axons of the VSF. Functional significance in the differences of 4‐AP sensitivity of the two motor systems is discussed. At opener motor axons, 4‐AP at 10 μM consistently increased AP amplitude, duration and after‐depolarization. At ventral superficial flexor (VSF), 4‐AP effects were less consistent. Changes in AP amplitude, repolarizing potential, firing frequencies and EPSPs were observed in some but not all axons. This mixture of positive and negative 4‐AP effects could be observed in the same animal. We propose that there is a significant diversity in the density of highly 4‐AP‐sensitive potassium channels among motor axons of the VSF.